Information Seeking in Knowledge Society: Choose Right from Wrong - Hassan, Zaiton; Hussin, Norhayati; Hashim, Hasnah; Tokiran, Nurul Syfa’ Mohd (International Journal of Asian Social Science, 2020)
In the era of born-digital, most of us nowadays always looking for the fastest way in the information-seeking process. The society has widely used the usage of internet as the information-seeking tools. However, the credibility of information vague without unknown information on the sources of that information. This paper will discuss how the knowledge society deals with the rapid changes in information and the information-seeking process. This paper also discusses the importance of being information literate and the importance of Media and Information Literacy skills to be adapted in the society as well as the discussion regarding the role of the information professional as a gatekeeper to the knowledge society and the importance of digital libraries in providing the right information for the society. Library and information professional is a key player to deliver the right and trusted information to the society and society can contribute towards developing the information society within their community.